inggris - Sukmawan, Rio; Sukiman (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
Microinsurance is emerging as an essential financial instrument within Islamic economics, focusing on principles of social justice, collective welfare, and equitable wealth distribution. This study investigates public perceptions and the factors influencing decisions to purchase microinsurance products among low-income communities in Indonesia. Despite the evolving awareness of insurance, skepticism and limited financial literacy persist, creating barriers to access. In line with Islamic economic principles, microinsurance offers a solution for inclusive financial protection through the application of ta'awun (mutual cooperation) and maslahah (public welfare), enabling the distribution of financial risks among participants without a focus on profit. This study emphasizes the potential of Sharia-based microinsurance in enhancing financial inclusion by providing affordable, accessible insurance products tailored to low-income individuals and micro-enterprises, particularly in sectors such as agriculture. The findings reveal key influencing factors: affordability, trustworthiness, simplicity, and community-driven support. Educating communities on the benefits of Sharia-compliant insurance is crucial for mitigating fatalistic beliefs and promoting a proactive approach to financial resilience. This research contributes to the broader discourse on financial inclusion, advocating microinsurance as a socially responsible and ethically aligned instrument within the Islamic economic framework to enhance financial security for vulnerable populations. Policymakers, too, have a role to play in creating an enabling environment that encourages the development and uptake of microinsurance as a vital tool for enhancing financial resilience among the vulnerable populations of Indonesia.